2022
DOI: 10.1371/journal.pone.0265811
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of hepatitis C and awareness of reinfection risk among people who successfully completed direct acting antiviral therapy

Abstract: Background Hepatitis C virus (HCV) education may be changing following the simplification of HCV treatment and emergence of direct acting antiviral (DAA). We aimed to characterize HCV knowledge among people who recently completed DAA therapy. Methods The Per-SVR (Preservation of Sustained Virologic Response) is a prospective cohort of patients who achieved a sustained virologic response upon successful completion of DAA therapy. The per-SVR study provided the sampling frame of participants who completed a ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Dalam penelitian Danish Nationwide Study, pendidikan rendah dikaitkan dengan peningkatan risiko infeksi HCV 1,35 kali lipat (95% CI: 1,20-1,52) dibandingkan dengan subyek berpendidikan tinggi (37). Dapat diasumsikan bahwa pendidikan yang lebih tinggi dan akses ke informasi medis secara substansial akan meningkatkan pengetahuan pasien tentang penyakit HCV (38,39). Penelitian sebelumnya menunjukkan bahwa orang yang terinfeksi HCV memiliki pengetahuan terbatas tentang penyakit HCV, terutama di daerah pedesaan (39).…”
Section: Pembahasanunclassified
“…Dalam penelitian Danish Nationwide Study, pendidikan rendah dikaitkan dengan peningkatan risiko infeksi HCV 1,35 kali lipat (95% CI: 1,20-1,52) dibandingkan dengan subyek berpendidikan tinggi (37). Dapat diasumsikan bahwa pendidikan yang lebih tinggi dan akses ke informasi medis secara substansial akan meningkatkan pengetahuan pasien tentang penyakit HCV (38,39). Penelitian sebelumnya menunjukkan bahwa orang yang terinfeksi HCV memiliki pengetahuan terbatas tentang penyakit HCV, terutama di daerah pedesaan (39).…”
Section: Pembahasanunclassified
“…Above all, the lack of awareness of infection is a major obstacle to the effectiveness of HCV elimination programs. It has been shown that almost 45% of those living with HCV were unaware of their infection status [ 11 ], and this has not changed much with time [ 12 ] In the US, the prevalence of HCV is disproportionate in some populations [ 13 , 14 ] A thorough report on the trends of self-awareness of HCV infection over the years and the difference in awareness between various demographic groups is vital to progress toward reducing the prevalence and transmission of HCV [ 15 ]. Apart from a better understanding of HCV awareness disparities, this can facilitate improved resource allotment and public health interventions.…”
Section: Introductionmentioning
confidence: 99%